The Hardships and Difficulties of Informal Carers Supporting People with Dementia - Štrancar, Anže (Ревија за социјална политика/Journal of Social Policy, 2024)
As the population ages, informal care is gaining increasing attention from both researchers and policymakers. The term informal carers refers to family members, friends, or neighbours of people with dementia who provide unpaid assistance and support. This article is based on research data collected as part of a larger research project conducted in Slovenia between 2020 and 2024. The aim of this article is to explore the challenges faced by informal carers supporting people with dementia in Slovenia and to identify the main characteristics of informal care in this context, in comparison to findings from studies in other countries. The data source for this study consists of five interviews with people with dementia and five interviews with informal carers, conducted in various regions of Slovenia over the project's duration. The findings of the study are consistent with those of research from other countries. For instance, in Slovenia informal caregiving for people with dementia is predominantly carried out by wives and daughters, highlighting a significant gender dimension to informal care. The interviewees reported experiencing similar challenges to those faced by caregivers in other countries. In particular, managing the demanding coordination of informal care with jobs and other responsibilities, such as household chores and family care, was highlighted. They also reported psychological strains associated with this role, noting that its time-consuming nature deprives them of opportunities to care for themselves.